2021
DOI: 10.1007/s40122-021-00340-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Benefit–Risk Assessment for Lidocaine 700 mg Medicated Plaster and Pregabalin in Peripheral Neuropathic Pain Following a Structured Framework Approach

Abstract: Introduction Peripheral neuropathic pain (PNP) is difficult to treat. Several oral drugs are recommended as first-line treatments. Nevertheless, many patients cannot obtain sufficient pain relief or do not tolerate systemically active treatments. Topical treatments, with a lower risk of systemic side effects such as lidocaine 700 mg medicated plaster, are also recommended in treatment guidelines. This analysis compares the benefit–risk balance of topical 700 mg lidocaine medicated plaster with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 44 publications
1
7
0
4
Order By: Relevance
“…Our findings support the previously reported good short-term and long-term tolerability of the plaster32 and the generally better adverse event profile compared with oral medications 33 34. A recent benefit/risk analysis showed that LMP had a more favorable benefit/risk balance compared with pregabalin (300 and 600 mg/day) for the treatment of peripheral neuropathic pain 35…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings support the previously reported good short-term and long-term tolerability of the plaster32 and the generally better adverse event profile compared with oral medications 33 34. A recent benefit/risk analysis showed that LMP had a more favorable benefit/risk balance compared with pregabalin (300 and 600 mg/day) for the treatment of peripheral neuropathic pain 35…”
Section: Discussionsupporting
confidence: 91%
“… 33 34 A recent benefit/risk analysis showed that LMP had a more favorable benefit/risk balance compared with pregabalin (300 and 600 mg/day) for the treatment of peripheral neuropathic pain. 35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lidocaine, depending on its form of administration, can have different problems, ranging from systemic side effects in its intravenous administration [ 19 ], to discomfort in the oral intake of pills, especially in the geriatric and pediatric population [ 20 ]. This tends to be a major challenge in medical issues and the topical alternative can present an unacceptable response time in many cases [ 9 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Outros efeitos nos queratinócitos e células imunes, ou ativação de receptores (TRPV1 e TRPA1), podem contribuir para o efeito analgésico da lidocaína. 45 É medicação de primeira linha da DN localizada, como neuralgia pós-herpética e lesão traumática de nervo periférico, onde a falta de efeitos colaterais sistêmicos a torna uma ótima opção (►Tabela 3). 12 O adesivo, emplastro de lidocaína 5%, deve ser utilizado por 12 horas, por dia, no máximo 3 unidades concomitantes, e por um período entre 2 a 4 semanas para que a resposta seja avaliada.…”
Section: Emplastro De Lidocaína 5%unclassified